Efficacy and Safety of Bexagliflozin, a Selective Sodium-Glucose Cotransporter-2 Inhibitor, in Type 2 Diabetes: A Systematic Review and Meta-Analysis - A.B.M. Kamrul-Hasan; Deep Dutta; Ershad Mondal; Lakshmi Nagendra; Mehedi Hasan; Md. Shahidullah; Kaushik Biswas; Saptarshi Bhattacharya (Clinical Diabetology)
OBJECTIVE: To summarize the therapeutic effect and safety of bexagliflozin in patients with type 2 diabetes (T2D). MATERIALS AND METHODS: Randomized controlled trials (RCTs) involving patients with T2D receiving bexagliflozin in the intervention arm and either a placebo or any active comparator in the control arm were searched through electronic databases. The primary outcome was the change from baseline (CFB) in glycated hemoglobin (HbA1c), and secondary outcomes included CFB in body weight, blood pressure, lipids, and adverse events. RevMan web was used to conduct meta-analysis using random-effects models. RESULTS: From 146 initially screened articles, data from nine RCTs involving 4,330 subjects were analyzed. Bexagliflozin outperformed placebo in terms of HbA1c reductions [standardized mean difference –0.55%, 95% CI (–0.68 to –0.42), p < 0.00001, I2 = 67%]; the degree of HbA1c reduction was similar whether bexagliflozin was used as monotherapy or as an add-on therapy. Higher proportions of subjects achieved HbA1c < 7% with bexagliflozin than in with placebo [odds ratio 2.73, 95% CI (1.80 to 4.14), p < 0.00001, I2 = 52%]. The CFB in HbA1c was identical with bexagliflozin and active comparators. Bexagliflozin had the additional benefits of reducing body weight and blood pressure and increasing HDL-C. Bexagliflozin and placebo had identical adverse event profiles. Compared to the active comparators, bexagliflozin imparted a lower risk of hypoglycemia and a higher risk of genital mycotic infection. CONCLUSIONS: The results of the meta-analysis support the convincing glycemic efficacy and safety profile of bexagliflozin in managing T2D.